Mars, Vénus, et Vulcain : l’image de la Chine dans les médias français sous l’ère Trump - Jean-Yves Heurtebise (MONDE CHINOIS NOUVELLE ASIE, 2016)
In a famous analogy, Robert Kagan opposed the United-States dedicated to the cult of Mars, manly god of wars, to Europe consecrating Venus, feminine goddess of pleasures. We would propose to extend this binary analogy by including China into it as representing Vulcan. Mars, Venus and Vulcan (Vulcan, god of braziers; China, factory of the world). How to understand the representational interactions between the United-States, Europe and China? In this triadic relation, from a European point of view, the United-States often served as a magnified image of itself (its bigger Self) while Chine served as a reversed image of itself (its remote Other). Moreover, the